2014
DOI: 10.1007/978-3-319-06025-5_33
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Epistemic Logic as a Substructural Logic

Guillaume Aucher

Abstract: Dynamic Epistemic Logic (DEL) is an influential logical framework for reasoning about the dynamics of beliefs and knowledge. It has been related to older and more established logical frameworks. Despite these connections, DEL remains, arguably, a rather isolated logic in the vast realm of non-classical logics and modal logics. This is problematic if logic is to be viewed ultimately as a unified and unifying field and if we want to avoid that DEL goes on "riding off madly in all directions" (a metaphor used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
0
0
1
Order By: Relevance
“…On the informational reading, substructural implication clearly resembles an information update operator; see also [3,4] where it is observed that dynamic epistemic logic can be seen as a twosorted substructural logic, and that the product update is a special case of the ternary accessibility relation. The question is, what kind of update operator does substructural implication represent?…”
Section: Ipal Substructural Logics and Dynamic Consequencementioning
confidence: 99%
“…On the informational reading, substructural implication clearly resembles an information update operator; see also [3,4] where it is observed that dynamic epistemic logic can be seen as a twosorted substructural logic, and that the product update is a special case of the ternary accessibility relation. The question is, what kind of update operator does substructural implication represent?…”
Section: Ipal Substructural Logics and Dynamic Consequencementioning
confidence: 99%
“…Формулы LTL позволяют формализовать такие утверждения как «ничего плохого никогда не произойдет» и «что-то хорошее, например, выполнение задач, будет происходить регулярно», поэтому они охватывают полезный набор спецификаций, связанных с регулярным достижением заданных целей без ущерба для безопасности системы [36]. В последующем, логика деревьев вычислений (CTL) и эпистемическая темпоральная логика начали применяться для работы с более сложными свойствами ДСС, например, свойством устойчивости, которое требует, чтобы система в конечном итоге достигла набора состояний, в которых выполняется какое-то утверждение, и оставалась там навсегда [37][38][39].…”
Section: Introductionunclassified